Trading Volume Activity Surrounding Earnings Releases: Evidence from Indonesia - Nainggolan, Rexon (JASF: Journal of Accounting and Strategic Finance, 2023)
The study investigates trading volume activities post-earnings announcement and their impact on abnormal returns. The objectives are to examine the changes in trading volume activities in response to earnings release and to measure the impact of the changes in trading volume activities on the cumulative average abnormal returns post-earning announcement. The study analyzes the trading volume response around the earnings announcement by comparing the ratio of trading volume activity (TVA) post-earnings announcements with the TVA during the estimation window. It reports an apparent increase in trading volume activity on day +2, indicating a slightly delayed reaction to the event's information. However, the findings indicate a significant relationship between cumulative abnormal returns and trading volume during the post-earning announcement abnormal return in a short period, following the semi-strong form of market efficiency. The study focuses on year-end announcements and does not evaluate interim announcements. The market response to interim data may vary and requires validation through an additional investigation. This implies that market traders should implement an effective trading strategy before the entire market reacts to the earnings announcement. Furthermore, the research findings underscore opportunities for policymakers to improve market infrastructure, hence augmenting the market's efficacy in conveying information pertaining to earnings releases.